Free vibration control of a cantilever MR fluid based sandwich beam - Romaszko, Mateusz (2013 14th International Carpathian Control Conference, 2013)
The subject of the paper is vibration control of a cantilever beam with magnetorheological (MR) fluid. Based on the results of identification and energy analysis, a simple semiactive vibration control algorithm for free vibrations of the beam based on switching the system equivalent stiffness between two distinct values was proposed. The algorithm was realized by controlling the current supplying the electromagnet. The MR fluid contained in the beam was activated by a magnetic field and under the impact of magnetic field enables the changing of its stiffness and damping properties. The free vibrations of the beam were investigated for constant current and current varied according to the assumed control algorithm.